Effect of black coffee and green tea on plasma C-peptide level in apparently healthy adults - Mittal, Anupam; Kumar, Pradeep; Singh, Shraddha; Ali, Wahid; Singh, Suresh Kumar; Chauhan, Pradeep Kumar (International Journal of Research in Medical Sciences, 2024)
Background: Black coffee and green tea, both known for their antioxidant properties and potential health benefits. Black coffee, rich in chlorogenic acid, is stimulating but can cause jitteriness due to its caffeine content. In contrast, green tea offers a balanced approach, with catechins providing anti-inflammatory effects and L-theanine promoting calm focus. In this study, we will investigate and compare the effects of black coffee and green tea on glucose metabolism and insulin sensitivity, aiming to deepen our understanding of their roles in managing metabolic health and related disorders. Methods: The study was conducted at King George’s Medical University, Lucknow, from April 1, 2023, to March 31, 2024, involved 140 healthy participants aged 20 to 30 years, divided into three groups: black coffee Group (35 participants), green tea group (35 participants), and lukewarm water control group (70 participants). Results: The study found no significant changes in plasma C-peptide levels after 21 days of consuming black coffee, green tea, or lukewarm water. Black coffee group (case), plasma C-peptide p=0.224. Green tea group (case), plasma C-peptide p=0.768. Lukewarm water group (control), plasma C-peptide p=0.491. All p values were above 0.05, indicating no significant effect of the beverages on these metabolic markers. Conclusions: The study concluded that neither black coffee nor green tea had a significant impact on plasma C-peptide levels in the short term. However, further research with larger sample sizes and varied demographics is recommended to validate these findings and explore long-term effects.